A Voltage Gain-Controlled Modified CFOA And Its Application in Electronically Tunable Four-Mode All-Pass Filter Design - Norbert Herencsar; Jaroslav Koton; Abhirup Lahiri; Bilgin Metin; Kamil Vrba (International Journal of Advances in Telecommunications, Electrotechnics, Signals and Systems, 2012)
This paper presents a new active building block (ABB) called voltage gain-controlled modified current feedback amplifier (VGC-MCFOA) based on bipolar junction transistor technology. The versatility of the new ABB is demonstrated in new first-order all-pass filter structure design employing single VGC-MCFOA, single grounded capacitor, and three resistors. Introduced circuit provides all four possible transfer functions at the same configuration, namely current-mode, transimpedance-mode, transadmittance-mode, and voltage-mode. The pole frequency of the circuit can be easily tuned by means of DC bias currents. The theoretical results are verified by SPICE simulations based on bipolar transistor arrays AT&T ALA400-CBIC-R process parameters.